The Effect of Return on Asset, Investment Opportunity Set and Firm Size on Earnings Management - Arie Cahyani; Fitria, Maulidah; Lestari, Ayu Ambang (Universitas Pamulang, 2025)
This study aims to examine the influence of Return on Assets (ROA), Investment Opportunity Set (IOS), and firm size on earnings management in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. Earnings management refers to the deliberate actions by management to influence financial reporting outcomes to meet specific objectives, such as maintaining a favorable image among investors. Based on signaling theory, management conveys information to the market as a signal of the firm’s future prospects, often represented through reported earnings. This study adopts a quantitative approach using purposive sampling, resulting in 14 selected companies and a total of 70 observation data points. The analytical method employed is multiple linear regression with classical assumption testing. The results indicate that ROA, IOS, and firm size do not simultaneously have a significant effect on earnings management. Individually, none of these independent variables significantly influence earnings management. These findings suggest that profitability, investment opportunities, and firm size are not the main factors driving earnings management practices in the property and real estate sector. Other factors outside the model may play a more dominant role in shaping managerial behavior related to earnings reporting.